PENGARUH MODEL PEMECAHAN MASALAH DAN KREATIVITAS TERHADAP HASIL BELAJAR IPA MATERI SISTEM PENCERNAAN MAKANAN MANUSIA SISWA DI SDN 060856 MEDAN - Restar Tarigan (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2018)
This study aimed to analyze The influence of science learning outcomes ofstudents. This study isa quasi experimental research (quasi experiment). This population is the class V SD 060856 Medan. The samplein this study selected by purposive random sampling as much as two grades. The instrument used consisted of: science achievement test and learning creativity questionnaire sheet. Data analysis was performed using ANOVA two lanes. The results of this study indicate that the learning outcomes of students that learned Science with problem solving learning model is significantly different and better than the students that learned by direct instruction learning. Studentswith high creativity indicates higher learning outcomes than students with low creativity. In this study shows there is an interaction between the learning model and the level of creativity in influencing student Science learning outcomes. Keywords: Learning Outcomes, Creativity, Solution Of ProblemThis study aimed to analyze The influence of science learning outcomes ofstudents. This study isa quasi experimental research (quasi experiment). This population is the class V SD 060856 Medan. The samplein this study selected by purposive random sampling as much as two grades. The instrument used consisted of: science achievement test and learning creativity questionnaire sheet. Data analysis was performed using ANOVA two lanes. The results of this study indicate that the learning outcomes of students that learned Science with problem solving learning model is significantly different and better than the students that learned by direct instruction learning. Studentswith high creativity indicates higher learning outcomes than students with low creativity. In this study shows there is an interaction between the learning model and the level of creativity in influencing student Science learning outcomes. Keywords: Learning Outcomes, Creativity, Solution Of Problem